Simultaneous detection of mixed ‘Candidatus Phytoplasma asteris’ and ‘Ca. Liberibacter solanacearum’ infection in carrot - SATTA, Eleonora; RAMIREZ, Ana; PALTRINIERI, Samanta; CONTALDO, Nicoletta; BENITO, Purifacation; POVEDA, José; BERTACCINI, Assunta (Phytopathologia Mediterranea, 2017)
Symptoms of shoot and root malformation were observed in carrot plants in fields located in the North of Gran Canaria Island (Spain), during surveys carried out in spring 2015 and 2016. Total DNA extraction from the leaves of symptomatic plants was performed and PCR assays were carried out to detect the agents possibly associated to the observed symptoms. While ‘Candidatus Liberibacter solanacearum’ was detected in the majority of tested symptomatic samples, phytoplasmas belonging to the ribosomal group 16SrI were detected only in two samples. Phylogenetic analyses and sequencing, together with virtual RFLP, confirmed that ‘Ca. L. solanacearum’ strains detected in carrot samples belong to haplotype D.